Nitrogen management in zero-tillage cum surface seeded wheat at Rampur, Chitwan, Nepal - Dahal, KR; Adhikari, BB; Basnet, KB (Agronomy Journal of Nepal, 2013)
An experiment was conducted at the experiment field of the Institute of Agriculture and Animal Sciences, Rampur, Chitwan, Nepal in 1999/2000 to assess the effect of mulch and the timing of nitrogen application on the performance of surface seeded wheat crop under zero-tillage condition. The experiment consisted of eight treatments that included 1/2 dose of N at sowing and 1/2 at crown root initiation (CRI) stage; 1/2 dose of N at 11 days after sowing and 1/2 at CRI; whole dose of N at CRI stage; and 1/2 dose of N at CRI and 1/2 40 days after sowing, with and without mulch using rice straw @ 4 ton/ha. The result showed that mulch was effective in conserving soil moisture, suppressing weeds and enhancing yield and yield attributing parameters. Similarly, application of nitrogen at two splits i.e. 1/2 dose of N at CRI and 1/2 at 40 days after sowing with mulch produced significantly higher grain yield (4547 kg/ha) whereas significantly lower grain yield (2267 kg/ha) was obtained from the treatment of 1/2 dose of N at sowing and 1/2 at CRI without mulch. DOI: http://dx.doi.org/10.3126/ajn.v1i0.7547 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.85-93